Mis-cut direction of substrate effect on the photoresponse characteristic of β-Ga2O3 film. (April 2022) - Ma, Y.J.; Zhang, X.D.; Feng, B.Y.; Tang, W.B.; Chen, T.W.; Qian, H.; Zhang, L.; Zhou, X.; Wei, X.; Xu, K.; Fu, H.Q.; Zhang, B.S.
Abstract: β-Ga2 O3 epitaxial film was grown on 6° mis-cut angle (toward <11 2 ‾ 0> and <10 1 ‾ 0> directions) c -plane sapphire substrate by metalorganic chemical vapor deposition (MOCVD). The influence of mis-cut sapphire substrate on β-Ga2 O3 film and the photoresponse properties of β-Ga2 O3 photodetectors were studied. Compared with non-miscut substrates, both mis-cut sapphire substrates can obtain high crystal quality β-Ga2 O3 films by reducing the in-plane rotational symmetry and promoting the step flow growth mode. Compared with the mis-cut toward <11 2 ‾ 0> direction, the substrate of mis-cut toward <10 1 ‾ 0> direction showed the highest crystal quality and largest growth rate due to smaller edge step terrace width and large step density. Three β-Ga2 O3 photodetectors were fabricated on films grown on the non-miscut and the two mis-cut substrates. The photoresponse characteristics of β-Ga2 O3 photodetectors based on sapphire substrate of mis-cut toward <10 1 ‾ 0> direction can reach 65 μA (photocurrent), 3.5 × 10 3 ( I p - I d / I d ) and 3.21 A/W (responsivity, under 254 nm light). These results demonstrate an important guidance to develop the industrialization of β-Ga2 O3 materials and devices. Highlights: The effects of sapphire substrates with different mis-cut directions on the β-Ga2 O3 thin films and the photoresponse properties of β-Ga2 O3 photodetectors were investigated. The effect of the step terrace width on the growth modes was analyzed. High quality β-Ga2 O3 thin films were epitaxially grown by MOCVD on mis-cut sapphire substrates. β-Ga2 O3 photodetectors with a metal-semiconductor-metal (MSM) structure have been fabricated and excellent optical performance were obtained.